Purchasing Decision: Shopping Momentum, Shopping Experience, and Price Discounts as Mediators on the Shopee Platform in the Gerbangkertosusila Region - Fredi Aldi Pratama; M. Mustaqim (Universitas Nahdlatul Ulama Sidoarjo, 2025)
The intense competition in the Indonesian e-commerce industry demands that platforms capture the driving factors of consumer purchasing decisions. This study aims to analyze the direct influence of Shopping Momentum and Shopping Experience on Purchase Decisions, as well as examine the role of Price Discounts as a mediating variable in this relationship. Using an explanatory quantitative approach, the research sample is Shopee users in the Gerbangkertosusila area selected through purposive sampling. This study has 170 active Shopee platform users in the Gerbangkertosusila area selected through a purposive sampling technique. Primary data were collected through a self-administered questionnaire and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with SmartPLS 4.0. This implies that price discounts function as a crucial trigger mechanism, effectively converting the positive impact of psychological conditions (shopping momentum) and cognitive evaluations (shopping experience) of users into actual purchasing actions.